Therapeutic Effect of Gum Arabic on some Biochemical Parameters in Nephrotoxic Albino rats - Eman Aboud Hussein; Husham Qassim Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
The aim of the current study is to evaluate some biochemical parameters in rats treated with gentamicinto induce nephrotoxicity . The experimental study was conducted using 42 healthy adult male rat weighing250-300 grams . The results showed a significant increase (P?0.05) in the levels of urea and creatinine inthe blood serum, an increase in the activity of liver enzymes AST, ALT, ALP and a significant decrease inthe concentration of albumin in adult male rats injected with gentamicin (80 mg / kg IP daily for 10 Days)to induce nephrotoxicity compared to control group. The results showed a significant increase (P?0.05)in the concentration of urea and creatinine in the blood serum and a significant increase (P?0.05) in theactivity of liver enzymes AST, ALT, ALP, and albumin concentration in (untreated induced nephrotoxicity)compared with (control group). The results showed a significant decrease (P?0.05) in the levels of ureaand creatinine in the blood serum and a significant decrease (P?0.05) in the activity of liver enzymes AST,ALT, ALP, kidney weight and a significant increase (P?0.05) in albumin concentration, from the inducednephrotoxicity group treated with (15% w / v / day) Gum Arabic compared to the untreated nephrotoxicgroup, but the values In all treated groups were less than the control group. The present study concluded thatthe induced nephrotoxicity group treated with Gum Arabic showed improvement in some biochemical andhematological parameters associated mainly with nephrotoxicity